Poverty, income inequality and living standards in Ireland: Third annual report - Roantree, Barra; Doorley, Karina (ESRI, 2023)
This report is the third from an ESRI research programme funded by Community Foundation Ireland, which seeks to address gaps in our knowledge and understanding of poverty, income inequality and living standards in Ireland. It builds on the previous reports which have found that while Ireland has experienced strong and progressive – if volatile – income growth over the past three decades both before and after accounting for housing costs, levels of income poverty and material deprivation have remained consistently high for certain groups (notably lone parents and those in working-age households where no one is in paid work). This year’s report finds the following in relation to the evolution and distribution of material living standards in Ireland. Income growth and inequality 2021 saw disposable incomes fall or stall for those in the bottom half of the distribution. Whereas real disposable income adjusted (equivalised) for household composition has grown robustly – and by more at the bottom than the middle or top of the distribution – since 2012, the latest data from the Survey of Income and Living Conditions (SILC) suggest incomes fell in real terms at the very bottom of the distribution between 2020 and 2021 and stalled across much of the rest of the distribution. These sluggish patterns of growth are despite a strong labour market recovery in 2021 and predate the sharp rise in prices that followed the invasion of Ukraine in early 2022. While the easing of COVID restrictions saw 200,000 more people employed on average in 2021 than 2020, employment earnings for those at the bottom of the household income distribution fell, due to a combination of a reduction in usual hours worked and fewer months worked full-time per year. This occurred before the sharp rise in prices that followed the invasion of Ukraine in early 2022, which are likely to further erode real incomes unless we experience levels of nominal income growth last seen in 2006 and 2007. Measures of income inequality – which have seen a sustained decline in recent years, reaching their lowest recorded levels in 2020 – increased in 2021. This is true both before and after accounting for housing costs, and serves as an important reminder that growth in employment and individual earnings – even when focused on low-paid workers – is not necessarily enough to ensure inclusive growth in disposable household incomes. It also highlights the crucial role tax and transfer policy play in underpinning inclusive growth, especially for the living standards of the poorest. Income poverty and material deprivation Although both before housing costs (BHC) and after housing costs (AHC) measures of income poverty were stable, 2022 saw a sharp – statistically significant – rise in the rate of material deprivation. The share of individuals unable to afford two or more items from a list of ten essentials rose from 13.3 to 16.6 per cent in 2022, with rates particularly high among lone parents (42 per cent), those renting from an approved housing body, local authority or receiving HAP (45.6 per cent), and those in households where no one of working age was in paid work (53.8 per cent). While those aged 65+ face a higher AROP rate than other age groups in terms of BHC income, children have consistently faced higher rates of material deprivation and AHC income poverty. Children living in households renting their accommodation and where no one is in paid work are at particularly high risk of poverty and material deprivation. Reducing child poverty The Government faces a challenge in reducing levels of child poverty, something it has placed a renewed emphasis on with the establishment of a Child Poverty and Well-being Programme Office in the Department of the Taoiseach. A substantial body of evidence finds that income poverty has a negative causal impact on child and later life outcomes, particularly when it starts in early childhood and persists throughout. Nevertheless, policymakers must confront a difficult set of trade-offs in pursuing reductions in child poverty with the current set of tools available. While increasing universal Child Benefit would reduce the child poverty rate and the poverty gap, it is substantially more costly to do so for each percentage point reduction than reforms to targeted means-tested payments like IQCs (Increases for a Qualified Child) and WFP (Working Families Payment). On the other hand, reforms to these more targeted payments have the potential to either weaken financial work incentives for recipients (because IQCs are primarily linked to stringently means-tested benefits) or to bypass the very lowest-income children (because WFP is contingent on a parent(s) working at least 38 hours per fortnight). Introducing a new Child Income Support Payment (CISP) would enable policymakers to reduce child poverty more effectively. Such a reform – which would provide all households with children to receive a payment determined by their means and number of children – has been recommended by the Commission on Taxation and Welfare (2022), National Economic and Social Council (2007; 2021) and the Childrens Rights Alliance (2010) among others. We estimate that such a reform has the potential to reduce child poverty by a quarter and the child poverty gap by half at a cost of around €700 million. However, in undertaking such a reform, the Government will have to confront some of the implicit choices made by the structure of the current welfare system that are rarely discussed, such as whether the welfare system should incentivise low-income individuals to engage in part-time work.
Published